TOTAL KOLESTEROL CONDITIONS ON CONSUMPTION OF BLACK POWDER COFFEE (Traditional) WITH PATIENT PREPARATION - Maruni Wiwin Diarti; Yunan Jiwintarum; Ida Ayu Reka (poltekkes kemenkes mataram, 2018)
Abstract: A traditional black coffee powder is one of the beverages that excessively consumed by communities. The increasing of total cholesterol level in blood is influenced by the habit of consuming coffee. Coffee has chemicals that can cause some health problems, namely cafestol and kahweol. The objective study was to determine the effect of patient preparation against the result of total cholesterol levels examination on the consumers of traditional black coffee powder. This research was analytic observational. The sample was capillary blood of consumers’ a traditional black coffee as many as 30 people. Statistical analysis utilized Mann-Whitney U Test with 95% confidence level (α = 0,05). The findings indicated the average deviation of total cholesterol level after fasting 12,86 mg / dL and mean difference after giving coffee 7 cups 18,46 mg / dL. Mann Whitney Test found significant value 0.001 <α = 0.05 which means there is an influence of patient preparation against the result of total cholesterol levels examination on the consumers of traditional black coffee powder.Keywords: Total Cholesterol Level; Consumers of Traditional Black Coffee Powder.